2022
DOI: 10.1186/s40168-022-01389-7
|View full text |Cite
|
Sign up to set email alerts
|

Colonocyte-derived lactate promotes E. coli fitness in the context of inflammation-associated gut microbiota dysbiosis

Abstract: Background Intestinal inflammation disrupts the microbiota composition leading to an expansion of Enterobacteriaceae family members (dysbiosis). Associated with this shift in microbiota composition is a profound change in the metabolic landscape of the intestine. It is unclear how changes in metabolite availability during gut inflammation impact microbial and host physiology. Results We investigated microbial and host lactate metabolism in murine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…54 In contrast, intestinal inflammation destroyed the composition of the microbiota, leading to the expansion of Enterobacteriaceae members. 55 Escherichia – Shigella is a member of Enterobacteriaceae and is proportional to the degree of skin itching and positively correlated with most pro-inflammatory factors in mice, 56 but negatively correlated with the integrity of the colonic barrier. Escherichia – Shigella causes macrophage apoptosis by penetrating epithelial cells and releasing IL-β to aggravate intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…54 In contrast, intestinal inflammation destroyed the composition of the microbiota, leading to the expansion of Enterobacteriaceae members. 55 Escherichia – Shigella is a member of Enterobacteriaceae and is proportional to the degree of skin itching and positively correlated with most pro-inflammatory factors in mice, 56 but negatively correlated with the integrity of the colonic barrier. Escherichia – Shigella causes macrophage apoptosis by penetrating epithelial cells and releasing IL-β to aggravate intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, generation of purines is governed by two pathways that work in combination to maintain energy balance; namely the de novo purine biosynthesis pathway and the salvage pathway. De novo synthesis is an energetically intensive metabolic process requiring eleven catalytic steps, five enzymes requiring ATP, and three amino acids to generate one molecule of IMP from PRPP [ 39 ]. Conversely, salvage directly forms IMP from PRPP and Hpx, leaving energy available to fuel other cellular processes, such as nucleic acid synthesis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that LDHD is involved in the regulation of copper apoptosis by controlling intracellular copper levels through involvement in the fatty acylation process of proteins in the TCA cycle ( 77 , 78 ). LDHD is expressed in intestinal epithelial cells and is involved in the regulation of oxidative stress and cellular metabolism, and it is believed that altered LDHD gene expression may lead to oxidative stress and altered cellular metabolism, resulting in increased intestinal inflammation ( 79 ), but the exact mechanism of its association with the development of UC is not fully understood.…”
Section: Discussionmentioning
confidence: 99%